Peer approach in developing resistance skills on sex and drugs among adolescents - Duka, Francis Grace H. (2006)
This study attempted to provide a worthwhile model of peer education by exploring the patterns and trends involved in the process of peer approach. Pertinent data were gathered mainly through participant observation in the Timbayog Peer Education Program in Casiguran, Sorsogon. It was supplemented by other relevant sources such as the researcher's diary, the Peer Educators' Journal, information sheets, and feedback forms. The study revealed that physical and social settings affect the quality of interaction in peer classes. Development of resistance skills among the peer students was facilitated by the modeling behavior of the peer educators and their provision of interactive activities and practice exercises in the peer classes, showing that resistance skills have multiple modalities. The local culture is revitalized by the development of resistance skills through the peer approach.
"March 2006."
Thesis (M.A. Education : Health Education)--University of the Philippines, Diliman.
Keywords: Teenagers -- Philippines -- Casiguran (Sorsogon) -- Attitudes; Teenagers -- Sexual behavior -- Philippines -- Casiguran (Sorsogon).; Teenagers -- Drug use -- Philippines -- Casiguran (Sorsogon).